Diversity among satellite glial cells in dorsal root ganglia of the rat - R.S. Nascimento; M.F. Santiago; S.A. Marques; S. Allodi; A.M.B. Martinez (Brazilian Journal of Medical and Biological Research, 2008)
Peripheral glial cells consist of satellite, enteric glial, and Schwann cells. In dorsal root ganglia, besides pseudo-unipolar neurons, myelinated and nonmyelinated fibers, macrophages, and fibroblasts, satellite cells also constitute the resident components. Information on satellite cells is not abundant; however, they appear to provide mechanical and metabolic support for neurons by forming an envelope surrounding their cell bodies. Although there is a heterogeneous population of neurons in the dorsal root ganglia, satellite cells have been described to be a homogeneous group of perineuronal cells. Our objective was to characterize the ultrastructure, immunohistochemistry, and histochemistry of the satellite cells of the dorsal root ganglia of 17 adult 3-4-month-old Wistar rats of both genders. Ultrastructurally, the nuclei of some satellite cells are heterochromatic, whereas others are euchromatic, which may result from different amounts of nuclear activity. We observed positive immunoreactivity for S-100 and vimentin in the cytoplasm of satellite cells. The intensity of S-100 protein varied according to the size of the enveloped neuron. We also noted that vimentin expression assumed a ring-like pattern and was preferentially located in the cytoplasm around the areas stained for S-100. In addition, we observed nitric oxide synthase-positive small-sized neurons and negative large-sized neurons equal to that described in the literature. Satellite cells were also positive for NADPH-diaphorase, particularly those associated with small-sized neurons. We conclude that all satellite cells are not identical as previously thought because they have different patterns of glial marker expression and these differences may be correlated with the size and function of the neuron they envelope.